2008
DOI: 10.1002/dvdy.21787
|View full text |Cite
|
Sign up to set email alerts
|

Dnm3os, a non‐coding RNA, is required for normal growth and skeletal development in mice

Abstract: Dnm3os, a gene that is transcribed into a non-coding RNA (ncRNA), contains three micro RNAs (miRNAs), miR-199a, miR-199a*, and miR-214, whose functions remain unknown in mammals. In this study, we introduced the lacZ gene into the Dnm3os locus to recapitulate its expression pattern and disrupt its function. Dnm3os ؉/lacZ heterozygous embryos showed ␤-galactosidase activity, which reflected the authentic expression pattern of Dnm3os RNA. Most of the Dnm3os lacZ/lacZ homozygous pups died within one month of birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 36 publications
6
140
0
1
Order By: Relevance
“…miR-199a2 is located within the DNM3os transcription unit. This long noncoding RNA transcript is responsible for synthesis of the miRNA cluster containing miR-199a2 and miR-214 and is involved in skeletal development (42,43). Accordingly it was necessary to determine whether PlGF regulated synthesis of the long DNM3os transcript, as previously observed, or instead led to independent transcription of premir-199a2.…”
Section: Discussionmentioning
confidence: 94%
“…miR-199a2 is located within the DNM3os transcription unit. This long noncoding RNA transcript is responsible for synthesis of the miRNA cluster containing miR-199a2 and miR-214 and is involved in skeletal development (42,43). Accordingly it was necessary to determine whether PlGF regulated synthesis of the long DNM3os transcript, as previously observed, or instead led to independent transcription of premir-199a2.…”
Section: Discussionmentioning
confidence: 94%
“…44 DNM3os is required for normal growth, development, and survival as indicated by the finding that DNM3os-null mice die within a month of birth because of skeletal abnormalities that include osteopenia and defects in the skull and spine. 45 MiR-199a exhibits highly variable patterns of expression during development, differentiation, and in various diseases, and its actions are also very variable even with respect to the same gene target because such genes have cell-and context-specific functions. 42 Our data indicate that miR-199a-5p suppresses CCN2 in human or mouse HSCs via its direct targeting of the CCN2 3 0 -UTR and that diminished expression of miR-199a-5p in activated HSCs allows CCN2 and its downstream targets to be expressed.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, miR-199a* is also intronically encoded within the DNM3 gene, which is itself specifically expressed in SS [59]. Furthermore, miR-199a* is directly up-regulated by TWIST1 binding [60], which is in turn up-regulated in SS owing to the frequent gain of the encoding region. They also demonstrated that reduced miR-342 levels in SS resulted in a significant increase in apoptosis levels, but did not significantly affect cell proliferation levels.…”
Section: The Inverse Correlation Between Mir-342 and Mir-199amentioning
confidence: 91%